Fractional Dynamics 2011
DOI: 10.1142/9789814340595_0009
|View full text |Cite
|
Sign up to set email alerts
|

Foundations of Fractional Dynamics: A Short Account

Abstract: Applications of fractional dynamics have received a steadily increasing amount of attention during the past decade. Its foundations have found less interest. This chapter briefly reviews the physical foundations of fractional dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…For the example of broadband dielectric spectroscopy in glasses, generalized relaxation functions and susceptibilities based on Equation (70) have already been successfully compared to experiments [23,[29][30][31][32]. Theoretical, mathematical and experimental studies are encouraged to further explore the consequences of the generalized concept.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the example of broadband dielectric spectroscopy in glasses, generalized relaxation functions and susceptibilities based on Equation (70) have already been successfully compared to experiments [23,[29][30][31][32]. Theoretical, mathematical and experimental studies are encouraged to further explore the consequences of the generalized concept.…”
Section: Discussionmentioning
confidence: 99%
“…The limit gives rise to a family of one-parameter semigroups T h α (with family index α and parameter h) of ultra-long-time evolution operators [22,23].…”
Section: Equation (46) Impliesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hilfer showed that this transition from ordinary time derivative to fractional time derivative indeed arises in physical problems [34,37,38,40].…”
Section: Preliminariesmentioning
confidence: 96%
“…It should be noted that in the general case fractional differential equations are difficult to solve exactly even with special functions. A fractional embedding of an ordinary differential equation is not unique and different embeddings correspond to different microscopic physical models [8]. It also introduces sensitivity of the boundary conditions, which requires regularization procedures leading to Caputotype of derivatives.…”
Section: Introductionmentioning
confidence: 99%